Writing a successful thesis or dissertation : tips and strategies for students in the social and behavioral sciences - Lunenburg, Frederick C. (Corwin, 2008)
Written for both faculty and students, 'Writing a Successful Thesis or Dissertation' provides a comprehensive 'how-to' compendium for completing a master's thesis or doctoral dissertation.